Help me TripAdvisor! : Examining the relationship between TripAdvisor e-WOM attributes, trusts towards online reviews and travellers behavioural intentions - Mahat, Nur Zarifah Dhabitah (Array, 2020)
This paper aims to examine the impact of TripAdvisor reviews on behavioural intentions, basing on travellers' trust towards the e-WOM reviews. Four factors are proposed for building travellers’ trust and behavioural intentions: information quality, credibility, adoption and usefulness. Trust is expected to mediate the relationship between eWOM attributes and travellers’ behavioural intention. Data from 410 travellers were analysed using Partial Least Square-Structural Equation Modeling (PLS-SEM), and the findings show that TripAdvisor e-WOM attributes (information credibility, adoption and usefulness) significantly influence the traveller's trust. Besides, traveller behavioural intention was influenced considerably by TripAdvisor eWOM information credibility and usefulness. Lastly, trust in e-WOM significantly mediates travellers' behavioural intention. This paper confirms the importance of eWOM in the context of the tourism industry and travellers' trust and behaviour towards online review, which altered how consumers behave before deciding to travel.